A Single Drop of Water: Vulnerability, Invisibility, and Accountability in South Korean Theatre’s Moment of Crisis - Younghee, Park; Neideck, Jeremy (Performance Paradigm, 2020)
In early 2018, encouraged by the #MeToo movement sweeping the Western media landscape, Korean actor Park Younghee took to Facebook to write of her experiences of sexual harassment at the hands of a prominent theatre director and academic in the 1990s. While Younghee didn’t publicly name her abuser, it was not long before the social media machine identified Oh Tae Suk as the man she alluded to, and his world-renowned Geukdan Mokwha as the site of her abuse. Days later, prolific theatre director Kim Soo-hee made allegations of violence and sexual abuse against Lee Yoon-taek, the artistic director of the juggernaut theatre company Yeonhuidan Georipae, setting off a firestorm in the South Korean Media that has yet to die down. In South Korea, public performances of grief, allyship, and holding the government to account are hallmarks of democratic transformation. In this article, Park Younghee tells parts of her story to longtime collaborator Jeremy Neideck, and they attempt to weave a coherent narrative out of their yearlong discussion about the social, cultural, and political histories of Korea. This article seeks to illuminate, but not necessarily explain, the environments in which men like Lee Youn-taek and Oh Tae Suk were able to perpetrate abuse.
Keywords: Bibliographie; Nettoyer; Raphaël

A Nonbinary Actor Prepares (for Battle) - Woodzick, K. Bylines (Theatre Topics, 2020)
Publisher: Johns Hopkins University Press
Keywords: Bibliographie; Nettoyer; Raphaël

Contemporary Feminist Protest in Ireland: #MeToo in Irish Theatre - Fitzpatrick, Lisa (Irish University Review, 2020)
This essay draws upon the work of Judith Butler, Sara Ahmed, and Germaine Greer to consider the #MeToo movement and its reflection in the work of the author's students and the scandal at Dublin's G...
Publisher: Edinburgh University Press
Keywords: #MeToo; Bibliographie; Contemporary Feminism; Intergenerational; Intersectional; Nettoyer; Raphaël; Teaching